Keeping conflict constructive : and unleashing the power of divergent thinking - Roberto, Michael A. (FTPress Delivers elements., 2011)
This Element is an excerpt from Why Great Leaders Don't Take Yes for an Answer: Managing for Conflict and Consensus (ISBN: 9780137000630) by Michael A. Roberto. Available in print and digital formats. Promoting constructive dialogue--and keeping it from degenerating into destructive, dysfunctional argument. In many organizations, debates become dysfunctional before the leader recognizes the warning signs. Diagnosing these situations as they unfold represents a critical leadership capability. How does a leader discern whether a passionate debate among his advisers and subordinates stands on the verge of becoming dysfunctional? Imagine two scenarios....